ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PERUM BULOG DIVRE AMBON - Maximiliane L C Hukom (JURNAL MANAJEMEN, 2014)
Writing aims to acknowledge and analyse about the accounting system sales at Perum Bulog Divre Ambon. This writing using this type of data are classified into primary data and secondary data. Next were analyzed using the methods of analysis deskritif. Accounting information system sales at Perum Bulog Divre Ambon is a blend of process information system and procedures that form a network that closely, and are inseparable from each other, all accounting activities and other major activities, in order to streamline all other major activities of an enterprise so that supervision by the command can be run as well as possible and achievable goals efficiently. Results of the research in deskritif that the application of the accounting information system sales at Perum Bulog Divre can provide information for the leadership of the company, it is seen in the preparation of the information systems and procedures, sales, Procurement, transaction evidence recording of transactions to reporting information is adequate because the evidence of the transaction created some duplicate ordinal number, given the evidence, the transactions are recorded on a daily basis based on evidence of a transaction, there is code in the same transaction estimates, are grouped as well as making accounting information system reports. For the process of classification the transactions, the company has also been using the method of approximate estimation of where the code has been standardized in the form of a guidebook with explanations and usage. Keyword : accounting system